Design and development of tapered slot antenna - He, Yuyue (2014)
This final year project studied optimal design of wideband Vivaldi antennas for ultra-wideband radar applications with high range resolution. After a literature review and comparison between two types of Vivaldi antennas, namely, antipodal Vivaldi antennas and tapered slot antennas, tapered slot antenna type is selected as the basic antenna type in the design.